ANALYSIS OF VISUAL ELEMENTS AND RESPONSES OF GENERATIONS Z ON COCA-COLA “THE GREAT MEAL” ADVERTISING VIDEO - I Made Verdy Natha Biantara Putera; Rai Gilang Atmadhi; Ni Putu Raka Laksmi Arpin; Putu Chrisma Dewi; Putu Chris Susanto (LPPM Universitas Dhyana Pura, 2021)
ABSTRACTSince this COVID-19 pandemic, many companies are trying to makeadvertising videos related to the current situation, one of them is a big companythat produces soft drinks, Coca-Cola. This research aims to analyze the visualelements of Coca-Cola’s “The Great Meal” advertising video (2020). The visualanalysis was conducted by using Kress and van Leeuwen‘s theory of visualgrammar from the point of view, angle, and narration of the video. Subsequently,the authors compare the analysis with the responses from four participants(Generation Z) using the video elicitation interview method to see if IndonesianGeneration Z participants fully understand the messages or moral values conveyedby Coca-Cola’s “The Great Meal” advertising video. From this study, it can beconcluded the Coca-Cola advertising video has fulfilled the cognitive purpose that itseeks to convey and hoped to be able to increase the awareness of other peopleregarding the brand.Keywords: video advertising, visual elements, generation Z, visual grammar,Covid-19 Pandemic